2013
DOI: 10.1016/j.jpurol.2011.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of endoscopic treatment of vesicoureteral reflux in children: Comparison of different bulking agents

Abstract: Clinically and radiologically, Dx/HA exhibited the best results, giving better protection against UTIs and a better VUR cure rate. There was still a risk of VUR recurrence in successfully treated children after 3 years of follow up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 36 publications
0
20
0
5
Order By: Relevance
“…14,15 The variable degree of ingrowth of native fibroblasts, the shrinkage of the bulking agent, and the reported immunological reactions after injection of collagen are reasons why cross-linked bovine collagen has been abandoned by most centres.…”
Section: Bulking Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 The variable degree of ingrowth of native fibroblasts, the shrinkage of the bulking agent, and the reported immunological reactions after injection of collagen are reasons why cross-linked bovine collagen has been abandoned by most centres.…”
Section: Bulking Agentsmentioning
confidence: 99%
“…24 A systematic review has shown an overall success rate per ureter of 77% at three months, while a German study noted a success rate of 81.5% at three months. 25,26 Many groups have compared the results obtained with a single injection of PDMS vs. Dx/HA copolymer for VUR endoscopic treatment. The results are variable, ranging from no difference to a better success rate with PDMS.…”
Section: Bulking Agentsmentioning
confidence: 99%
“…It is the most studied material, offering good success rates, with available long-term data of at least 3 years. 5,6 However, Dx/HA is not the perfect bulking agent; its success rate varies widely, 7 as it has a significant recurrence rate and shows 25% shrinkage in the following weeks following the injection. 8 Moreover, Dx/HA is expensive and the cost of endoscopic treatment has increased over the years mainly because of the increase in the amount of product needed to be injected.…”
Section: Introductionmentioning
confidence: 99%
“…DISKUSIJA REZULTATA Obrađeni su podaci 50 pacijenata (ukupno 79 ureteralnih jedinica), lečeni u Univerzitetskoj dečjoj klinici. Distribucija prema polovima u ovoj studiji je 24% dečaka i 76% devojčica, što je očekivano i približno se poklapa sa polnom distribucijom iz durgih studija [10,11]. Starosna struktura pacijenata je od 18 meseci do 11 godina, dok su se u drugim studijama prikazivali rezultati na znatno širem starosnom opsegu od uzrasta od nepunih mesec dana pa do preko 15 godina (10, 11, 2).…”
Section: Rezultatiunclassified
“…adolescentima kod kojih konzervativni tretman nema uspeha (1). I u drugim studijama nije bilo dece sa prvim gradusom refluksa koji su uključeni u studiju (12,13,11), dok je najviše bio zastupljen gradus III (13). Gradus V u našoj studiji bio je zastupljen sa 10.2%, manje nego u stidiji Chertina i saradnika [13], dok pojedini autori nisu uzimali u obzir gradus V [11].…”
Section: Rezultatiunclassified